Effects of anthropogenic disturbance on primate density at the landscape scale. Issue 4 (27th February 2019) - Cavada, Nathalie; Tenan, Simone; Barelli, Claudia; Rovero, Francesco
Abstract: Accurate estimations of the abundance of threatened animal populations are required for assessment of species' status and vulnerability and conservation planning. However, density estimation is usually difficult and resource demanding, so researchers often collect data at local scales. However, anthropogenic pressures most often have landscape‐level effects, for example, through habitat loss and fragmentation. We applied hierarchical distance sampling (HDS) to transect count data to determine the effect of habitat and anthropogenic factors on the density of 3 arboreal primate species inhabiting 5 distinct tropical forests across a landscape of 19, 000 km 2 in the Udzungwa Mountains of Tanzania. We developed a novel, multiregion extension of HDS that allowed us to model density and detectability jointly across forests without losing site‐specific information. For all species, the effect of anthropogenic disturbance on density was overwhelmingly negative among metapopulations: −0.63 Angolan colobus (Colobus angolensis palliatus) (95% Bayesian CI −1.03 to −0.27), −0.54 Udzungwa red colobus (Procolobus gordonorum) (−0.89 to −0.22), and −0.33 Sykes' monkey (Cercopithecus mitis monoides) (−0.63 to −0.07). Some responses to habitat factors were shared, notably the negative effect of elevation and the positive effect of climber coverage. These results are important for conservation science and practice because: the among‐populations negative responses to anthropogenic disturbance provides a foundation for development of conservation plans that hold at the landscape scale, which is a comprehensive and cost‐efficient approach; the among‐species consistency in responses suggests conservation measures may be generalized at the guild level, which is especially relevant given the functional importance of primates in tropical rainforests; and the greater primate densities in areas at low elevation, which are closer to human settlements, point to specific management recommendations, such as the creation of buffer zones and prioritization of areas for protection. Abstract : Article impact statement : Upscaling abundance estimation at metapopulation level provides a foundation to address human disturbance in fragmented landscapes. Abstract : Efectos de la Perturbación Antropogénica sobre la Densidad de Primates a Escala de Paisaje Resumen: Se requieren estimaciones correctas del tamaño de las poblaciones de animales amenazados para evaluar el estado y la vulnerabilidad de las especies y así planear su conservación. Sin embargo, la estimación de la densidad es usualmente complicada y demanda recursos, así que los investigadores con frecuencia recolectan la información a escala local, a pesar de que la presión antropogénica suele tener efectos a nivel del paisaje; por ejemplo, la pérdida del hábitat y la fragmentación. Aplicamos un muestro jerárquico a distancia (HDS, en inglés) para contar datos por transecto y determinar el efecto de los factores del hábitat y los factores antropogénicos sobre la densidad de tres especies de primates arbóreos en un paisaje de 19, 000 km 2 en las montañas de Udzungwa en Tanzania. Desarrollamos una novedosa extensión multiregión de HDS que nos permitió modelar en conjunto la densidad y la facilidad de detección en los bosques sin perder información específica del sitio. Para todas las especies, el efecto de la perturbación antropogénica sobre la densidad fue abrumadoramente negativa entre las metapoblaciones: −0.63 para el colobo angoleño (Colobus angolensis palliatus) (95% bayesiano CI de −1.03 a −0.27), −0.54 para el colobo rojo de Udzungwa (Procolobus gordonorum) (de −0.89 a −0.22), y −0.33 para el mono de Syke (Cercopithecus mitis monoides) (de −0.63 a −0.07). Los monos compartieron algunas respuestas a los factores de hábitat, notoriamente los efectos negativos de la elevación y el efecto positivo de la cobertura de plantas trepadoras. Estos resultados son importantes para la ciencia y práctica de la conservación ya que: las respuestas negativas a las perturbaciones antropogénicas entre las poblaciones proporcionan los cimientos para el desarrollo de planes de conservación que serán válidos a nivel de paisaje, la cual es una estrategia completa y rentable; la consistencia de las respuestas entre las especies sugiere que las medidas de conservación pueden estar generalizadas a nivel de gremio, lo cual es de suma relevancia dada la importancia funcional de los primates en los bosques tropicales; y la densidad mayor de primates en áreas con elevación baja, las cuales están próximas a los asentamientos humanos, señalan hacia recomendaciones específicas de manejo, como la creación de zonas de amortiguamiento y la priorización de áreas para proteger. 摘要: 物种濒危等级、易危性的评估及保护规划需要对濒危动物种群数量进行准确估计。但是密度估计通常较为困难, 且对资源的需求较高, 因此研究者一般只能收集局部尺度的数据。然而, 人为压力的影响常常是景观尺度的, 例如导致生境丧失和破碎化。我们在坦桑尼亚乌德宗瓦山脉 (Udzungwa Mountains) 19, 000 平方千米的景观尺度中, 采用分层距离取样法收集样带计数数据, 确定了生境和人为因素对三种栖息在五个不同的热带森林树栖灵长类物种种群密度的影响。我们发展了一种新的多区域分层距离取样法, 可以在不丢失位置特异信息的情况下对跨越多个森林的物种种群密度和可探测性统一建模。对所有这三个物种来说, 人为干扰对集合种群密度的影响整体上都是负面的: 安哥拉疣猴 ( Colobus angolensis palliatus) 为 −0.63 (95 % 贝叶斯置信区间为 −1.03 到 −0.27); 乌德宗瓦红疣猴 ( Procolobus gordonorum) 为 −0.54 (95 % 贝叶斯置信区间为 −0.89 到 −0.22); 青猴 ( Cercopithecus mitis monoides) 为 −0.33 (95 % 贝叶斯置信区间为 −0.63 到 −0.07) 。它们对生境因素的响应有共同之处, 特别是海拔的负面影响和攀缘植物覆盖度的积极作用。这些结果对保护科学和实践十分重要, 因为种群间对人为干扰共同的负面响应为发展景观尺度上的保护计划提供了基础, 这样的保护实践更为全面且成本效益高; 物种间的响应一致性则表明保护措施可能可以推广到多物种水平, 考虑到灵长类动物对热带雨林的重要功能, 这一点意义重大; 而灵长类在海拔低、与人类居住地较近的地区密度更高, 这指明了具体的管理建议, 例如确立缓冲区和优先保护区域。【翻译: 胡怡思; 审校: 聂永刚】